The contribution of cysteine residues to antigenicity and extent of processing of herpes simplex virus type 1 glycoprotein D. - Wilcox, W C (1988)
Glycoprotein D (gD) is an envelope component of herpes simplex virus types 1 (gD-1) and 2 (gD-2). The gD-1 polypeptide contains seven cysteine residues among its 369 amino acids; six are located on the N-terminal or luminal portion of the glycoprotein, and a seventh is located in the transmembrane region. Previous studies used a panel of monoclonal antibodies (MAbs) to define gD epitopes as continuous or discontinuous. Purified gD, denatured by reduction and alkylation, loses discontinuous epitopes, whereas continuous epitopes are retained. The contribution of disulfide bonds to maintenance of discontinuous epitopes is, therefore, significant. In the present study, our objective was to determine the contribution of individual cysteine residues to folding of gD-1 into its native conformation. Site-directed oligonucleotide mutagenesis was used to create seven mutants, each with a serine residue replacing a cysteine. The mutated genes were cloned into a eucaryotic expression vector and transfected into COS-1 cells, and the proteins were separated by nondenaturing polyacrylamide gel electrophoresis, followed by immunoblotting. Replacement of cysteine 7 (residue 333) had only a minimal effect on the antigenic properties of gD-1. In contrast, replacement of any one of the other six cysteine residues resulted in either a major reduction or a complete loss of binding of those MAbs that recognize discontinuous epitopes, with no effect on the binding of MAbs which recognize continuous epitopes. These mutations also had profound effects on the extent of oligosaccharide processing of gD-1. This was determined by digestion of the expressed proteins with various endoglycosidases, followed by electrophoresis and Western blotting (immunoblotting) to observe any mobility changes. Three mutant gD proteins which did not express discontinuous epitopes contained only high-mannose-type oligosaccharides, suggesting that processing had not proceeded beyond the precursor stage. Two mutant forms of gD exhibited reduced binding of MAbs to discontinuous epitopes. A small proportion of the molecules which accumulated at 48 h posttransfection contained complex oligosaccharides. One mutant exhibited reduced binding of MAbs to discontinuous epitopes, but was present at 48 h posttransfection only in the precursor form. The cysteine 7 mutant was processed to the same extent as wild-type gD. We conclude that the first six cysteine residues are critical to the correct folding, antigenic structure, and processing of gD-1, and we speculate that they form three disulfide-bonded pairs.